Integrating Models of Collaborative Consultation and Systems Change to Implement Forgiveness-Focused Bullying Interventions. Issue 1 (2nd January 2016) - Skaar, Nicole R.; Freedman, Suzanne; Carlon, Amy; Watson, Elizabeth
Abstract : Through collaborative consultation with school staff, school psychologists have increasingly helped schools add bullying prevention and intervention programming to their service delivery systems. As schools search for ways to lessen the impact of bullying on the social-emotional health and academic achievement of students, forgiveness education is an area that may offer another perspective to bullying prevention and intervention. In order to infuse forgiveness education into schools' current tiered-service delivery systems, school psychologists and their district partners can use the frameworks of collaborative strategic planning (CSP) and the concerns-based adoption model (CBAM) in tandem to guide the development and implementation of forgiveness-focused bullying interventions at the core, supplementary, and intensive levels of a multitiered system of service delivery .